2019
DOI: 10.1155/2019/7145857
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antibacterial Activities of 1H-Imidazo [5, 6-f] [1,10] Phenanthroline-2(3H)-Thione and Its Ni(II) and Cu(II) Complexes

Abstract: As multidrug resistant pathogens are emerging, the search for novel potent drug candidates is ever going. Heterocycles are known by their broad spectrum of biological activities, so a search for a new drug from heterocycles can elevate the chance of success. e aim of this study was to obtain novel potent antimicrobial compounds. In line with this, 1H-imidazo [5, 6-f] [1,10] phenanthroline-2(3H)-thione and its complexes (Ni(II) and Cu(II)) were synthesized, characterized, and evaluated against bacterial strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Hence, the need to seek for an alternative combination for sulfamethoxazole which will also offer expanded spectrum of action against disease pathogens. Reported literatures have suggested that heterocycles and their derivatives have excellent broad spectrum of biological activities (Helio et al, 2006;Taghreed et al, 2015), so a search for a new drug from heterocycles is believed to support the chance of success (Tirkeso et al, 2019). Among the heterocycles, 1,10-Phenanthroline (phen) and 2,2′ bipyridine (bipy) have extended planar π systems and can be used in model compounds to copy the non covalent interactions in biological processes (Armani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the need to seek for an alternative combination for sulfamethoxazole which will also offer expanded spectrum of action against disease pathogens. Reported literatures have suggested that heterocycles and their derivatives have excellent broad spectrum of biological activities (Helio et al, 2006;Taghreed et al, 2015), so a search for a new drug from heterocycles is believed to support the chance of success (Tirkeso et al, 2019). Among the heterocycles, 1,10-Phenanthroline (phen) and 2,2′ bipyridine (bipy) have extended planar π systems and can be used in model compounds to copy the non covalent interactions in biological processes (Armani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%